delaneyh10
delaneyh10
01-02-2018
Mathematics
contestada
33 + 6x = 3(-1 + 5x)
Respuesta :
chrysanthemum
chrysanthemum
01-02-2018
33 + 6x = 3(-1 + 5x)
33 + 6x = -3 + 15x
33 = -3 + 9x
36 = 9x
4 = x
Answer
:
x = 4
Hope this helps.
Answer Link
iby909
iby909
01-02-2018
33+6x=-3+15x
33=-3+9x
36=9x
=4
Answer Link
VER TODAS LAS RESPUESTAS ( 86+ )
Otras preguntas
how many times does 20 go into 190
A _____ change occurs when a substance changes phase
How does the use of hydroelectric energy compare to the use of coal?
What is the purpose of the thesis statement in a research paper?
An important part of lending money and giving loans for the American System was the _____.
What is transferred by a force moving an object through a distance? A. force B. mass C. motion D. energy
In a college of exactly 2860 students , exactly 70% are male. What is the number of female students
The Paleolithic, Mesolithic, and Neolithic eras occurred during which age? A. the Iron Age B. the Brass Age C. the Stone Age D. the Bronze Age
Which type of organism is E. coli? restriction organism recombinant organism transgenic organism vector organism
Which one of the following vitamins helps prevent osteoporosis? A. Vitamin E B. Vitamin A C. Vitamin B D. Vitamin D